Severe bone disease caused by primary hyperparathyroidism: a case report and review of the literature - Yu Wang; Jie Liu (Journal of International Medical Research, 2020)
Bone disease is an important complication of hyperparathyroidism. We herein report a rare case of severe bone disease caused by primary hyperparathyroidism. A 33-year-old man presented with pain and restricted mobility in his right upper limb and right hip due to a fall 3 days previously. X-ray examination showed a fracture of the proximal and distal humerus. Computed tomography examination showed a supracondylar fracture of the right humerus, a fracture of the right femoral neck, a fracture of the right sciatic branch, and multiple brown tumors. Ultrasonography showed a 3.5- × 1.6-cm hypoechoic mass below the left lobe of the thyroid. The patient was diagnosed with primary hyperparathyroidism based on increased serum calcium and parathormone concentrations, pathological fractures, and multiple brown tumors. He therefore underwent bilateral lower parathyroidectomy. Pathological examination revealed a parathyroid adenoma. The patient recovered well after surgery and was followed up for 6 months with no symptoms of hyperparathyroidism. This case report suggests that clinicians should be aware of the possibility of severe bone disease secondary to primary hyperparathyroidism. Active and early diagnosis and surgical treatment are important in such cases.